Migrations of the rural population on the Polish-Moldavian borderland in the 16th century - Jawor, Grzegorz (Balcanica Posnaniensia. Acta et studia, 2021)
Historical studies are dominated by the belief that in the 16th century the trend of cross-border migrations between the lands controlled by the Polish-Lithuanian state and Moldavia was fading away. Hence, the settlement according the Vlach law, which was spreading at that time in Ruthenia, was supposed to be mainly the work of the local population or the ruthenized Vlachs who came to this area in the 15th century. The aim of the presented research was to confront this view with so far poorly used historical documents of quantitative nature, primarily inventories and lustrations of royal properties existing in Podolia. As a result, a significant intensity of migrations was found throughout the century. They ran in opposite directions: Moldavians (Vlachs) migrated to Poland and Ruthenians crossed the state border with Moldavia. Boundary region of Podolia was often only a temporary stop in this process. From this land, immigrants headed deeper into the country, actively participating in the process of establishing new shepherd settlements.